(3JOHjQ GdUMIs - (3GdbQWHj , ehSi Hf ejehf Hf YHjOGddg GdGSQGFjdj,J (B601 (3g` s
(3ChdgG (B:s
(3hQO Ydi Gdeedhc GdCUZQ ehSi Hf YHjO Gddg GdESQGFjdi GdbQWHi GdCeQ GdYGdi Gdehdhi GdCaVdi CYdGg Gddg hCjOg hCeVGg s
(3BNQgG (B:s
(3JfJgi HGdaUd GdMGOi YTQ ai CaVd dMhe GdUjO , Hbhdg hWHjN dMeg jbhi GdHUQ , hjaJM SOg UM HGdJLQHI hfbd Yf CaGVd GdCWHGA JeJ GdQSGdI s
(3GdfSNI HgG MhGTs
(3HgGghGeT hYfGhjf LGfHjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B43 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(1154 - (1)2061) s
Keywords: (3GdWHs